Development of a temperature-switch PCR-based SNP typing method for Mycobacterium ulcerans. - Katharina Röltgen; Kobina Assan-Ampah; Emelia Danso; Dorothy Yeboah-Manu; Gerd Pluschke (PLoS Neglected Tropical Diseases)
Mycobacterium ulcerans (M. ulcerans), the causative agent of the devastating skin disease Buruli ulcer (BU), is characterized by an extremely low level of genetic diversity. Recently, we have reported the first discrimination of closely related M. ulcerans variants in the BU endemic Densu River Valley of Ghana. In the study real-time PCR-based single nucleotide polymorphism (SNP) typing at 89 predefined loci revealed the presence of ten M. ulcerans haplotypes circulating in the BU endemic region. Here we describe the development of temperature-switch PCR (TSP) assays that allow distinguishing these haplotypes by conventional agarose gel-based analysis of the PCR products. After validation of the accuracy of typing results, the TSP assays were successfully established in a reference laboratory in Ghana. Development of the cost-effective and rapid TSP-based genetic fingerprinting method will thus allow investigating the spread of M. ulcerans clones by regular genetic monitoring in BU endemic countries.